Forensic examinations in cases of rampage killings Rechtsmedizinische Untersuchungen bei Amokfällen - Kamphausen, T.; Peschel, O.; Rothschild, M. A.; Janßen, K.; Banaschak, S. (Rechtsmedizin, 2017)
Background: Shooting rampages have occurred sporadically in Germany in recent years and were examined forensically. They differ from terrorist assaults less in terms of sequence than in terms of motivation. Objective: The current article describes the forensic examinations that are necessary for complete clarification of an incident. Particular focus is placed on their organization, since the opportunity to answer questions that might arise later is determined or limited predominantly by decisions governing the sequence and scope of the examinations. Materials and methods: On-site investigations; identification of afflicted persons; detection of injury patterns (in the living and the dead); investigation of the offender/suspect, including chemical-toxicological studies; consideration of the single acts; and a summarized analysis of the overall sequence constitute the spectrum of forensic investigation of rampage killings. All examinations are carried out in close cooperation with the investigating authorities. Results: Only the availability of postmortem computed tomography, which is increasingly employed, has extended the range of methods. This has also significantly improved documentation of bone injuries and localization of projectiles. Inadequate investigations or examination conditions can be problematic if questions that were not considered primarily, and which were thus not adequately examined or were even neglected, are raised publicly at a later stage. Conclusion: Examinations of victims of rampage killings differ from other forensic investigations in terms of circumstances, but not in terms of content. Thorough, comprehensive (and, as such, also time-consuming) documentation of findings is obligatory.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Disasters; Legal medicine; Offender; Strategic planning; Victim